RASD (International Library of African Music, 2015)
RASD is a song in entamas mode and medha rhythm directed at the PF and about the principles of the Saharawi constitution. Since 1976, these songs are performed by the group El Ualy (named for their hero), the first musical band representing the Saharawi people in exile.
Keywords: African Music